Legionella spp. in a Dental Office—Current State of Knowledge - Jolanta Szymańska (Pathogens, 2025)
Conditions in dental offices are conducive to Legionella pneumophila infections. This is mainly related to the use of a dental unit in the daily clinical work, which is the basic equipment of the office. Water discharged from the dental unit waterlines (DUWLs) and the working tips of the dental unit generates splatter/spatter and bioaerosol, constituting the main sources of potential infection and posing a health threat to both patients and professional dental staff. This article presents a narrative review on the presence and risk associated with Legionella spp., particularly the species L. pneumophila, in the dental office. This paper summarizes current knowledge and offers readers practical references, especially useful in everyday clinical dental practice.